Let there be light [gallium nitride LED]. - Zorpette, G.
The incandescent light bulb rolled back the night around the start of the 20th century. The gallium nitride LED will light the way in the 21st. The development of the gallium nitride (GaN) LED, made it possible to get white light from a semiconductor. GaN LEDs are already quietly transforming specialized illumination, including architectural and stage lighting, indoor and outdoor accent lighting, traffic and railway signaling, commercial and retail signs and displays, and outdoor illumination on bridges, walkways, gardens, and fountains. Lumen for lumen, white LEDs cost roughly 100 times as much as an incandescent bulb. Not to worry, say researchers. Not only will they get the cost down, they are going to dazzle us with devices that will be 10 times as efficient as an incandescent and will last 100 times as long. By mixing light from LEDs of different colors, the devices will provide 1000 shades of white-or any hue under the sun-at the twist of a dial.
Keywords: GaN; Architectural lighting; Displays; Gallium nitride LED; Indoor accent lighting; Outdoor accent lighting; Outdoor illumination; Railway signaling lighting; Retail signs; Specialized illumination; Stage lighting; Traffic signaling lighting; White light